UNHEARD/HEARD VOICES IN EXODUS 1-17 AND SOME THOUGHTS ON POVERTY IN SOUTH AFRICA - J.S. Van der Walt (Acta Theologica, 2019)
When someone cries, it usually signals that something is wrong or that there has been some kind of unsettling experience. One can cry because of emotional pain, physical pain and even anger. Crying is not always heard though. A cry of silence may not be noticeable, but this does not mean that there is less pain or emotion. In Exodus 1-17, the theme of crying is presented from different angles. This article focuses on different aspects of crying in the Exodus tradition, which starts with a silent cry, and on the so-called absence of YHWH, which, in fact, points to an undoubtedly absent presence. In conclusion, with insights drawn from the narrative text, the article offers some thoughts on the theme of poverty in South Africa, as unheard voices in this regard should also be heard, with the church being the most likely agent to deliver this message.